Optimasi Sistem Informasi Konsultasi Hukum melalui Pendekatan Pengujian Kombinasi White-box dan Black-box - Nurwicaksono, Muhammad Agy; Lisa, Irma Noor; Tiara, Astia Rahma; Sidik, Rangga (Jurnal Manajemen Informatika JAMIKA, 2024)
This study aims to test the legal consulting information system "Advogo" in the hope of finding deficiencies in the system that has been built, and opening up opportunities for improvement and further development of the system. Testing is done by 2 methods, white-box, and black-box testing. The white-box method used in this study is branch and basis path testing, while the black-box method used is the cause-effect graph. The limitation of white-box testing in this study is the SessionController.php file with Index, Create, Store, Show, and Update functions. While the limitations of the black-box are the creation of consultation sessions, authentication, and session bookings. The results of this study are the formation of 10 test cases for white-box testing with 100% valid results, and 14 test cases for black-box testing with 92% valid results, where there is 1 invalid test case so it is necessary to make improvements so that the system can function according to which are expected.